Employment and higher education in young adults with cerebral palsy: a cross-sectional analysis of the SPARCLE study - Catherine Arnaud; Mariane Sentenac; Ute Thyen; Kate Himmelmann; Virginie Ehlinger; Nicolas Vidart d'Egurbide Bagazgoïtia; Celia Perret; Carine Duffaut (BMJ Publishing Group, 2023)
Introduction For young people with disabilities, access to higher education and employment should lead to improved personal self-esteem and well-being and, in the long run, to increased inclusion in society. Our aims were to describe the education and employment status of young adults with cerebral palsy (CP), to investigate the personal and contextual factors, including prior mainstream education, that most influence these statuses, and to study to what extent employment affects the quality of life (QoL).Methods We used data from the SPARCLE3 cross-sectional study, collected in 2018-2020 in five European regions. Eligible participants were adults with CP, 22-27 years, without moderate to profound intellectual disability. Outcomes were education and employment statuses. Unconditional logistic regressions were performed to test the association with impairments, comorbidities, personal and family characteristics and environmental factors. QoL scores (WHOQOL-bref score 0-100) were compared using linear regressions.Results Of the 227 participants, 21.6% had a tertiary degree, 35.2% were employed. The likelihood of being employed or of having a tertiary degree was reduced by more than 75% for those with more severe gross motor limitations or communication/speech difficulties. Those with a tertiary degree were more likely to be employed (OR 9.37 (95% CI 2.87 to 30.64)) while accessible car parking was the only associated environmental factor (OR 2.92 (95% CI 1.19 to 7.18)). Prior mainstream schooling increased the odds of being employed 16-fold. Individuals who were employed reported an 8-point increase in the physical and psychological well-being domains of QoL compared with those who were unemployed.Conclusions The employment situation of young adults with CP can still be improved, but our findings encourage the implementation of inclusive policies from an early age.